Application of maslahah (interest) in deciding the right of hadanah (custody) of a child: the practice in the Syariah Court of Malaysia - Che Soh @ Yusoff, Roslina; Abdul Hak, Nora (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Firstly, this article briefly discusses the concept of maslahah in Islam. Relevant verses in the Qur’an and hadith of the Prophet Muhammad s.a.w are referred to show that the principle of maslahah has strong supportive authorities in Shariah. Secondly, the application of the principle of maslahah in custody dispute is deliberated. The application of the divisions of maslahah i.e., dharuriyyah, hajiyyah and tahsiniyyah is presented in detail. Relevant provisions of the Islamic Family Law Act/Enactment and decided cases of the Shariah Court are analysed to study the practice of the principle of child’s interest in Malaysia. Thirdly, conclusion is made emphasising on the importance of the Syariah Courts giving due consideration to this principle of maslahah in awarding the custody order. The study was mainly based on library research. It used Islamic legal research methodology. The benefit of this methodology is that through the study of the classical schools of legal thought of the Muslim jurists and the reasoning behind their rulings, a proper knowledge concerning the topic of the study has been acquired and this knowledge has been used to analyse the existing law and application of maslahah in Malaysia. Islamic legal research methodology is based on the study of the sources of law i.e., the Qur’an and the Sunnah and also other secondary sources of shariah. Basically, it involves a thorough study of the relevant literature on fiqh, tafsir and hadiths of the Prophet Muhammad of the recognised schools of Islamic law relating to the principle of maslahah in custody dispute.